FLIP Y SU APORTE EN EL PROCESO DE ENSEÑANZA-APRENDIZAJE DE LOS ESTUDIANTES DE BACHILLERATO TÉCNICO EN INFORMÁTICA, SECCIÓN VESPERTINA DE LA UNIDAD EDUCATIVA VINCES, PERIODO ACADÉMICO ABRIL - AGOSTO 2024 - LEON CAMPOVERDE GINGER DAYANA (2024)
This project determined the contribution of Flip in the teaching-learning process of the technical high school students in Computer Science, afternoon section of the Vinces Educational Unit, academic period April - August 2024, through exploratory and descriptive inquiry, surveys were carried out on the students. and the implementation of a training program aimed at teachers to evaluate whether the use of this technological platform highlights the flexibility and interactive dynamics for their training. This study examined how this tool contributes to improving academic training by providing a shared space to record, edit and share video assignments, facilitating access to feedback resources and facilitating fluid communication between students. The study began with a theoretical vision of educational training and the use of technologies in education, highlighting its types of learning strategies. The methods used to collect and analyze data were then described in details. In addition, we learned about the students, which particularly affects their academic performance. Finally, the investigation offered practical recommendations for the successful functioning of this tool in other educational contexts, demonstrating the need for continuous training of teachers and their students on how to use technology in their daily activities.